Temporal trends of thyroid cancer in China and globally from 1990 to 2021: an analysis of the global burden of Disease Study 2021 - Kaiyuan Huang; Xuanwei Huang; Shuoying Qian; Yuan Cai; Fan Wu; Dingcun Luo (Scientific Reports, 2024)
Abstract The incidence of thyroid cancer (TC) is increasing annually worldwide, with a growing burden. This study aims to analyze temporal trends in the burden of TC by age and sex in China and globally from 1990 to 2021, including incidence, prevalence, mortality, and disability-adjusted life years (DALYs) rates, and to predict future trends. We obtained data on TC in China and globally from 1990 to 2021 from the Global Burden of Disease (GBD) database. Using the Joinpoint regression model, we calculated and analyzed the trends in age-standardized incidence rate (ASIR), age-standardized prevalence rate (ASPR), age-standardized mortality rate (ASMR), and age-standardized DALYs rate (ASDR). Specifically, we estimated the annual percent change (APC), the average annual percent change (AAPC), and the corresponding 95% confidence intervals (95% CI) for each metric. Additionally, we conducted a decomposition analysis to investigate the impact of aging, population growth, and epidemiological factors on the incidence and mortality rates of TC. Furthermore, the autoregressive integrated moving average (ARIMA) model was employed to predict the burden of TC from 2022 to 2036.  From 1990 to 2021, the ASIR for TC in China increased from 1.249 (95% uncertainty interval [UI]: 1.009–1.473) per 100,000 to 2.473 (95% UI: 1.993–3.088) per 100,000. Conversely, the ASMR decreased from 0.473 (95% UI: 0.403–0.550) per 100,000 to 0.387 (95% UI: 0.307–0.472) per 100,000. Both males and females demonstrated an upward trajectory in ASIR. However, while the ASMR for females decreased, that for males showed an overall increase despite a decline in the last decade. The age of peak onset for TC ranged from 30 to 79 years, whereas the age of peak mortality was between 50 and 89 years. The analysis using the AAPC indicates that the growth in the ASIR (AAPC = 2.242, 95% CI: 2.112–2.371) and ASPR (AAPC = 2.975, 95% CI: 2.833–3.117) in China exceeds the global rate. Furthermore, the reduction in ASMR (AAPC = -0.651, 95% CI: -0.824 - -0.479) and ASDR (AAPC = -0.590, 95% CI: -0.787 - -0.392) in China is also more pronounced than globally. Decomposition analysis indicates that the increasing TC burden in China is primarily driven by population aging, whereas globally, population growth plays a more significant role. Projections based on predictive models suggest that from 2021 to 2036, the ASIR for both China and the global population is expected to continue rising, while the ASMR is anticipated to decline further.  The incidence rates of TC in China and globally have shown a continuous upward trend, which is expected to persist over the next 15 years. Additionally, although the number of male TC cases is relatively lower compared to females, the overall ASMR and ASDR for males have shown an upward trend, despite a slight decline in recent years. This highlights the need to enhance prevention, diagnosis, and treatment measures, and to develop differentiated screening and treatment strategies based on age and sex.